Analisis Pengendalian Kualitas menggunakan Metode Six Sigma pada Produk Roti Tawar di PT. Ital Fran’s Multindo Food Industries Cabang Bali - Setiawati, Ketut Lilis; Satriawan, I Ketut; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
The purpose of this study were to determine the factors of damage, to analysis of damage is still within control limits and to establish efforts to repair damaged bread products at PT. Ital Fran's Multindo Food Industries. Data analysis used the six-sigma method, with the stages of Define, Measure, Analyze, Improve (DMAI). The results of this study are the factors that cause product damage come from human factors, production machines, work methods and materials / raw materials. Damage to white bread products at PT. Ital Fran's Multindo Food Industries is in control limits or has good process capabilities. The average Defects Per Million Opportunities (DPMO) value was 3107.3874 and the average sigma value was 4.24, including sigma level 6. Proposed improvements that can be done to overcome damage to plain bread products, namely making Standard Operating Procedures for laying bread from the pan to the conveyor, monitoring and checking employee performance, making Standard Operating Procedures regarding the right temperature and standard time for removing bread, making Operational Standards Procedures regarding cleanliness in the production area and worker hygiene, carry out maintenance and cleaning of tools and machines on a regular basis. Keywords : quality control, six sigma, white bread